2016
DOI: 10.1007/s10509-016-2962-2
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation of Dirac monopoles from the global monopole black hole with quantum gravity effects

Abstract: In this paper we study the quantum tunneling of Dirac magnetic monopoles from the global monopole black hole under quantum gravity effects. We start from the modified Maxwell's equations and the Generalized Uncertainty Relation (GUP), to recover the GUP corrected temperature for the global monopole black hole by solving the modified Dirac equation via Hamilton-Jacobi method. Furthermore, we also include the quantum corrections beyond the semiclassical approximation, in particular, first we find the logarithmic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The timelike naked singularities of the black hole were discussed [16]. The Hawking radiations of the f (R) global monopole corrected black hole was considered based on the Heisenberg uncertainty principle or generalized uncertainty principle respectively [17,18]. Further, the absorption and scattering of an f (R)-global-monopole black hole have been investigated [19].…”
Section: Introductionmentioning
confidence: 99%
“…The timelike naked singularities of the black hole were discussed [16]. The Hawking radiations of the f (R) global monopole corrected black hole was considered based on the Heisenberg uncertainty principle or generalized uncertainty principle respectively [17,18]. Further, the absorption and scattering of an f (R)-global-monopole black hole have been investigated [19].…”
Section: Introductionmentioning
confidence: 99%
“…In [14], Dadhich et al studied the effect of global monopolar charge on particle orbits and Hawking radiation, and corrected the global monopole black hole Hawking radiation in [15]. In addition, Kimet and Gordana proposed the quantum tunneling effect of the Dirac magnetic monopole in a black hole with an integral magnetic monopole [16]. In 2016, researchers studied the mass fraction of the unipolar parameter and found that it can suppress the maximum accretion rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been found in many cases that the GUP has an important role in black hole physics, which is the emergence of black hole remnants [15][16][17][18][19][20][21][22][23]. In addition, in determining the entropy of black holes it has been found due to the effect of quantum gravity logarithmic corrections to the law of the area [24][25][26][27][28][29]. In [30], by considering the effect of the Lorentz invariance violation of dispersion relations, the Hawking radiation of the charged fermions via tunneling from the Reissner-Nordström black hole has been investigated.…”
Section: Introductionmentioning
confidence: 99%